The Effect of Android-Based Learning Media Using Crossword Puzzles On English Vocabulary Mastery - Rini Yudiati; Hanifatur Rizqi (Prisma Sains : Jurnal Pengkajian Ilmu dan Pembelajaran Matematika dan IPA IKIP Mataram, 2022)
The aim of the study were how is the application of Android-based learning media using Crossword Puzzles in learning English vocabulary for class XI students of SMKN I Sumenep, the effect and the respon of Students about crossword puzzles. This Study is a quasi-experimental with quantitative method using true experimental design for their control class and experiment. The sampel was 74 students that grouped into experimental class 38 student and control class 36 students. It is not taken randomly but chosen by the school authority. Data collection techniques used in this study is observation techniques, testing, and questionnaires. Analysis of the observation data carried out by theEnglish teachersobtained results of 92.55% at the first meeting and 94.31% at the second meeting. This is considered to have met the "very strong" criteria. In the statistical analysis of the data, the results obtained tcount = 4.80 and db = 70, with a significant level of 5%. With t count = 4.80 and db = 70, it is known that the price ts 0.05 = 2.00 indicates that t is greater than the t table (4.80 ≥ 2.00), which means that H0 is rejected and H1 is accepted. The results of the student response questionnaire on the use of android-based media through Crossword Puzzles on the mastery of English vocabulary showed a positive response with an average value of 61% -80% and 81% -100%. Thus, it can be concluded that Android-based learning media through Crossword Puzzleshas a significant effect on the mastery of English vocabulary for class XI students of SMKN I Sumenep.